Access after the earthquake: the micro politics of recovery and reconstruction in Sindhupalchok District, Nepal, with particular reference to caste. Issue 2 (3rd April 2019) - Bownas, Richard; Bishokarma, Ratna
Abstract : This article examines the aftermath of the Nepal earthquakes of 2015 with special reference to their impact on marginalized communities, in particular Dalit or 'Untouchable' communities in Sindhupalchok District, one of the worst affected districts of Nepal. The earthquakes not only took thousands of lives and destroyed property and livelihoods, but their aftermath has revealed the webs of power that shape and limit the opportunities of different communities. Referencing the theoretical approach to access pioneered by (Ribot, J., and N. Peluso. 2003. "A Theory of Access." Rural Sociology 68 (2): 153–181)the article proceeds to analyze the relative 'winners and losers' from the reconstruction process, finding a mixed picture of opportunities and barriers facing the most marginalized communities in the district.